Development of a robot-assisted reduction and rehabilitation system for distal radius fractures - Zha, Qing; Xu, Zeou; Yang, Hongbo; Zhang, Guodong; Cai, Xuefeng; Zhang, Wanlin; Liu, Yujiang; Shen, Xiaofeng; Li, Yuwei (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Closed reduction is the preferred treatment for distal radius fractures. However, it requires a multiple experienced medical staff and manually maintaining stable traction is difficult.Additionally, doctors cannot assess the reduction status of a fracture in real-time through radiographic images, which may lead to improper reduction. Furthermore, post-fracture complications such as joint adhesion, stiffness, and impaired mobility pose a challenge for the doctors. So it is necessary to optimize the treatment process of the distal radius fracture through technological means.Methods: A robot-assisted closed reduction and rehabilitation system, which could assist doctors throughout the entire process of reduction, fixation, and rehabilitation of distal radius fractures, was developed. A mechanical system, composed of two grippers and a cooperative robotic arm, was used to grasp and tract the affected limb. A doctor controlled the robot through a joystick console and Windows application program. A biplane radiographic device was integrated into the system, which is not only convenient for doctors to view radiographic images of the fracture at any time but also for them to select the rotation axis of the wrist on the images before reduction and rehabilitation.Important information including the anteroposterior and lateral radiographic data and force and position parameters during the reduction and rehabilitation process were displayed on a graphic user interface.Experimental results showed that the proposed robotic system can meet the technical requirements for the reduction and rehabilitation of distal radius fractures, all the rotation angles could be achieved, a maximum force of more than 50 N could be achieved in all traction directions, and the error in selecting the wrist joint rotation axis line using radiographic images was less than 5 mm.The developed robot-assisted system was shown to be suitable for closed reduction and rehabilitation of distal radius fractures, contributing a potential improvement in the quality of the procedures.